2008
DOI: 10.2337/dc07-1443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Glucose Homeostasis

Abstract: OBJECTIVE -To examine the effect of aging on insulin secretion (first-and second-phase insulin release) and insulin sensitivity in people with normal glucose tolerance (NGT) or impaired glucose tolerance (IGT).RESEARCH DESIGN AND METHODS -First-and second-phase insulin secretion and insulin sensitivity were assessed in hyperglycemic clamp experiments in 266 individuals with NGT and 130 individuals with IGT, ranging in age from ϳ20 to ϳ70 years. Changes in ␤-cell function were compared using the disposition ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(109 citation statements)
references
References 34 publications
8
99
0
2
Order By: Relevance
“…Although decreased insulin sensitivity is reported to occur with age, we found that both hepatic and peripheral insulin sensitivity were similar in YS and OS subjects. While the absence of age-related declines in insulin sensitivity is in contrast with numerous previous reports (4,21,30,31), our results are consistent with a growing body of literature indicating that adiposity and physical activity levels, rather than chronological age, are primary determinants of age-related declines in insulin sensitivity (32)(33)(34)(35)(36). In support of this notion, we find that fat mass, abdominal adiposity, and BMI were significant predictors of R d during the clamp.…”
Section: Nrf1supporting
confidence: 89%
“…Although decreased insulin sensitivity is reported to occur with age, we found that both hepatic and peripheral insulin sensitivity were similar in YS and OS subjects. While the absence of age-related declines in insulin sensitivity is in contrast with numerous previous reports (4,21,30,31), our results are consistent with a growing body of literature indicating that adiposity and physical activity levels, rather than chronological age, are primary determinants of age-related declines in insulin sensitivity (32)(33)(34)(35)(36). In support of this notion, we find that fat mass, abdominal adiposity, and BMI were significant predictors of R d during the clamp.…”
Section: Nrf1supporting
confidence: 89%
“…Decrease in beta cell proliferation capacity and enhanced sensitivity to apoptosis are the states related with aging (Maedler et al, 2006). A study by Szoke et al (2008) showed that the first and second phase of insulin secretion normally decreases at the rate of approximately 0.7% per year with aging, this decrease in cell function is accelerated about two-fold in people with impaired glucose tolerance. But aging per se has no effect on insulin sensitivity independent of change in body composition.…”
Section: Age and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Similarly, a positive correlation of fasting plasma glucose (FPG) with age has been reported from some studies [5,6] but not in others [7,8]. The ageing of populations may further increase the burden of type 2 diabetes and pre-diabetes [impaired fasting glucose (IFG)/IGT] on health care systems worldwide [9]. Knowledge of the impact of age on IR together with β-cell function and glucose metabolism may have clinical implications in intervention and management of pre-diabetes and diabetes in elderly populations.…”
Section: Introductionmentioning
confidence: 99%